Natural Analogue Constraints on Europa's Non‐ice Surface Material. Issue 11 (4th June 2019) - Fox‐Powell, Mark G.; Osinski, Gordon R.; Applin, Daniel; Stromberg, Jessica M.; Gázquez, Fernando; Cloutis, Ed; Allender, Elyse; Cousins, Claire R.
Abstract: Non‐icy material on the surface of Jupiter's moon Europa is hypothesized to have originated from its subsurface ocean and thus provide a record of ocean composition and habitability. The nature of this material is debated, but observations suggest that it comprises hydrated sulfate and chloride salts. Analogue spectroscopic studies have previously focused on single‐phase salts under controlled laboratory conditions. We investigated natural salts from perennially cold (<0 °C) hypersaline springs and characterized their reflectance properties at 100, 253, and 293 K. Despite similar major ion chemistry, these springs form mineralogically diverse deposits, which when measured at 100 K closely match reflectance spectra from Europa. In the most sulfate‐rich samples, we find that spectral features predicted from laboratory salts are obscured. Our data are consistent with sulfate‐dominated europan non‐icy material and further show that the emplacement of endogenic sulfates on Europa's surface would not preclude a chloride‐dominated ocean. Plain Language Summary: Europa, a moon of Jupiter, has become a priority target in the search for life off the Earth, due to the presence of a liquid water ocean under its icy shell. Salts on the moon's surface might originate from this ocean and therefore offer a way of studying the ocean without requiring direct access. Our knowledge of these salts comes from comparing spacecraft measurements to pure salts produced in laboratories. We have studied natural salts from hypersaline springs in the Canadian Arctic as an alternative, complementary approach. Measuring samples from these deposits at europan surface temperatures, several unexpected properties were observed, including the absence of spectral details predicted by previous laboratory studies. This challenges some of the estimates of europan surface composition. Natural analogues such as these will form part of an integrative approach to understanding data from upcoming missions, such as the National Aeronautics and Space Administration's (NASA) Europa Clipper and the European Space Agency's JUpiter ICy moons Explorer. Key Points: Low‐temperature hydrated salts from the Canadian Arctic provide geochemical and spectral analogues for europan surface material Qualitatively different deposits can form from fluids with similar major ion chemistry Endogenic sulfates on Europa would not rule out a chloride‐dominated ocean